JURIDICAL ANALYSIS OF MANAGEMENT OF FOREIGN FISHERY SHIP CRIME OF FISHERIES IN THE EXCLUSIVE ECONOMIC ZONE (EEZ) OF INDONESIA (Research Study at Batam Marine and Fishery Resources Supervision Base Office) - Syamsu Rokhman, Muhammad (RADJA PUBLIKA, 2022)
Illegal fishing is a fishing activity that is contrary to the law in a particular country and international law. The forms of fishing theft practices that occur in Indonesian waters include fishing without a permit using a fake permit, catching fish using fishing gear that has been prohibited and catching fish species that are not in accordance with the applicable permit. This study uses a normative juridical method, namely by discussing the law that is conceptualized as written in the applicable laws and regulations and is linked or proven by facts in the field which is supported by empirical legal research (practice in the field) to obtain data. primary. The results of the study show that law enforcement in each country has different ways of dealing with the problem of fishing theft, one of which is Indonesia, policies against illegal fishing by taking action against foreign vessels have a positive impact, actions against illegal fishing in accordance with Law No. 45 of 2009 concerning Fisheries concerning amendments to Law Number 31 of 2004 and also international law of UNCLOS 1982. Based on the results of the study, it can be concluded that in an effort to handle criminal acts in the field of fisheries (Illegal Fishing) Indonesia as a country that has ratified UNCLOS (United Nation Convention in the Law of the Sea) has the authority and sovereignty to enforce laws relating to domestic interests in waters bordering other countries,